The application of murotal therapy as an alternative to address anxiety in pregnant women in the third trimester facing childbirth - Cut Yuniwati (Institute of Computer Science (IOCS), 2023)
Anxiety is a significant concern for expectant mothers, particularly in the third trimester. Various therapeutic approaches have been developed to address this issue, including Murotal Al-Quran therapy. This study aims to evaluate the effectiveness of Murotal Al-Quran therapy in managing anxiety during the third trimester. A comprehensive review of previous studies consistently demonstrates its positive impact in reducing anxiety levels among pregnant women. Reciting the Quran and incorporating Quranic verses in therapy have proven effective in reducing anxiety, depression, and enhancing emotional well-being. It also shows potential in influencing physiological responses, such as lowering blood pressure and stabilizing heart rate. By establishing a spiritual connection and promoting reflection, pregnant women can find inner tranquility. However, it is essential to acknowledge that Murotal Al-Quran therapy should be complemented with social support, counseling, and medical care for a holistic approach to anxiety management during pregnancy. By adopting this comprehensive approach, Murotal Al-Quran therapy becomes a valuable tool in preparing pregnant women mentally and emotionally for childbirth. It has shown promising results in alleviating anxiety and enhancing overall well-being, supporting pregnant women through the challenges of pregnancy and childbirth.